Differentiation Syndrome; Post-ATRA/ATO Induction Therapy in Acute Promyelocytic Leukemia: Acute Promyelocytic Leukemia - Karim, Kanwal; Pervaiz, Simab; Majeed, Ina Abdul; Mushtaq, Sana; Arshad, Hina (Pakistan Journal of Health Sciences, 2023)
Acute promyelocytic leukemia (APL) is a disease described as definite morphological and cytogenetical abnormalities and leads to coagulopathy leaving the patient in a life-threatening condition. A specific chromosomal translocation of 15 and 17 chromosomes leads to retinoic acid receptor-α (RARα) and promyelocytic leukemia (PML) genes fusion that produces an abnormal gene mutation forming an oncogenic protein which is (PML-RARα). Those APL patients, who have been treated with all-trans retinoic acid (ATRA) or arsenic trioxide (ATO) commonly lead a complicated condition called differentiation syndrome which is rarely severe. This case report explains the 37-years old male diagnosed with acute promyelocytic leukemia and later developed a differentiation syndrome after initiation of all-trans retinoic acid and arsenic trioxide induction therapy.